The Equity Trap, the Cost of Capital and the Firms Growth Path - Tobias Lindhe; Jan Södersten (Uppsala University, Department of Economics, 2006)
This paper reconsiders Sinns (1991) nucleus theory of the corporation by comparing two different regimes for the equity trap. In the first of these, all cash paid to the shareholders is taxed as dividends, in the second, shareholders are allowed a tax-free return of capital contributed through new issues. A substantial difference is found between the regimes in the seize of initial equity injections, although in both regimes, no dividends are paid until a new long-run equilibrium is reached. Contrary to Sinn, we find that with optimal behavior, the cost of new equity is lower than suggested by conventional formulae.
urn:nbn:se:uu:diva-13254
Keywords: H24; H25; H32; 330; dividend taxation; equity trap; cost of capital; nucleus theory; growth path; Kapitalertragsteuer; Kapitalkosten; Unternehmenswachstum; Aktionäre; Verhaltensökonomik; Theorie